2020
DOI: 10.7759/cureus.10053
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Patients With Restless Leg Syndrome: Can We Relieve Their Suffering?

Abstract: Restless leg syndrome (RLS), also called Willis Ekbom disease, can be described as an unpleasant feeling that intensely urges the patients to move their lower limbs. RLS is classified into primary and secondary. It is one of the common complications in hemodialysis patients, and it impairs patients' quality of life. Unfortunately, it is an underdiagnosed and undertreated disorder. In this review article, we performed a literature search using the PubMed database to compare different treatment modalities for RL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The following steps to the pharmacologic therapies shall consider the severity and impact of symptoms and the side effects 121. In contrast, Salib et al122 stated that we should consider their general condition, financial status, other comorbidities, and conditions unrelated to the kidneys. Figure 2 shows the different treatment modalities used in hemodialysis patients with RLS.…”
Section: Methodsmentioning
confidence: 99%
“…The following steps to the pharmacologic therapies shall consider the severity and impact of symptoms and the side effects 121. In contrast, Salib et al122 stated that we should consider their general condition, financial status, other comorbidities, and conditions unrelated to the kidneys. Figure 2 shows the different treatment modalities used in hemodialysis patients with RLS.…”
Section: Methodsmentioning
confidence: 99%
“…Hemodialysis patients experiece a variety of bothersome clinical symptoms, such as carpal tunnel syndrome [ 6 , 7 ], restless leg syndrome [ 8 , 9 ], pruritus [ 8 , 10 ], poor appetite [ 8 , 11 , 12 ], anemia [ 13 ], and insomnia [ 14 ]. Some of these symptoms can be explained by the incomplete removal of middle high molecular weight uremic toxins during hemodialysis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 It has been reported that RLS in patients on hemodialysis is also associated with the morbidity and mortality of cardiovascular diseases. 14,15 The pathogenesis may be related to factors such as hyperphosphatemia, transferrin saturation < 20%, lower hemoglobin level, insufficient erythropoietin response, chronic inflammation, and oxidative stress. 14,16 However, the specific pathogenesis needs further research.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The pathogenesis may be related to factors such as hyperphosphatemia, transferrin saturation < 20%, lower hemoglobin level, insufficient erythropoietin response, chronic inflammation, and oxidative stress. 14,16 However, the specific pathogenesis needs further research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation